ChemInform Abstract: Nitrosylation of Hexafluoridotechnetate(IV). Issue 28 (21st June 2013) - Balasekaran, Samundeeswari Mariappan; Molski, Matthias; Hagenbach, Adelheid; Abram, Ulrich
Abstract [Tc(NO)(NH3)4F]4[TcF6] [HF2]2 is obtained in almost quantitative yield by reaction of K2[TcF6] with acetohydroxamic acid (Ac‐NH‐OH) in aqueous HF solution.